Chlorpromazine attenuated electroacupuncture analgesia in conscious rabbits - Dai Jia-Le; Xu Shao-Fen (Acta Pharmacologica Sinica, 2016)
By measuring the defense behavior in response to the noxious stimulation induced by potassium iontophoresis on ear-lobe skin of conscious rabbit, chlorpromazine (CPZ) (0.5 mg.kg-1, i.v.) induced hyperalgesia, whereas it significantly attenuated electroacupuncture analgesia (EAA) efficacy. Monoamines and their metabolites in cerebrospinal fluid (CSF) were measured by high pressure liquid chromatography with electrochemical detector (HPLC-ECD) while the attenuation effect of CPZ on EAA was observed. CPZ markedly enhanced 3,4-dihydroxyphenylacetic acid (DOPAC) (P < 0.05) and homovanillic acid (HVA) (P< 0.01) contents in CSF both in the presence and absence of electroacupuncture. CPZ attenuated EAA with elevations of either DOPAC or HVA concentrations in CSF. There was a positive correlation between the increase of DOPAC or HVA content in CSF and the attenuation effect of CPZ on EAA (P < 0.05). These results suggested that the activation of dopamine system was unfavorable for EAA.